Contextualizing inclusive education in educational policy: the case of Sweden. Issue 2 (4th May 2019) - Magnússon, Gunnlaugur; Göransson, Kerstin; Lindqvist, Gunilla
ABSTRACT: In this article, we regard inclusive education as a policy phenomenon that contains a range of ideas about the purpose of education, the content of education and the organization of education. As a political ideal expressed in policy, inclusive education competes with other political ideals regarding education, for instance economic discourses that prioritize effectivity and attainment as educational goals. Thus, inclusive education has to be realized in contexts where available options for action are restricted by several and often contradictory educational policies on different levels of the education system. We argue that while research and debate about inclusive education are important, both are insufficient without analyses of the context of national educational policy. Any interpretation of inclusive education is necessarily situated in a general education policy, and measures of what ‘inclusive schools’ are dependent upon for instance, political interpretation(s) of inclusive education, resource allocation and political discourse on both local and national educational level. Here, we will provide support for this argument through presentation of both research on inclusive education, an alignment of prior analyses of Swedish national education policies and our own analyses of government statements.